2020
DOI: 10.7554/elife.49834
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement biases subsequent perceptual decisions when confidence is low, a widespread behavioral phenomenon

Abstract: Learning from successes and failures often improves the quality of subsequent decisions. Past outcomes, however, should not influence purely perceptual decisions after task acquisition is complete since these are designed so that only sensory evidence determines the correct choice. Yet, numerous studies report that outcomes can bias perceptual decisions, causing spurious changes in choice behavior without improving accuracy. Here we show that the effects of reward on perceptual decisions are principled: past r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
166
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(181 citation statements)
references
References 49 publications
14
166
1
Order By: Relevance
“…Previous studies have shown that animals shift their decision boundary even without reward amount manipulations in perceptual decision tasks ( Lak et al, 2020a ). These shifts occur on a trial-by-trial basis, following a win-stay strategy, choosing the same side when that side was associated with reward in the previous trial, particularly when the stimulus was more ambiguous ( Lak et al, 2020a ). In the current task design, however, the optimal bias is primarily determined by the sizes of reward (more specifically, which side delivered a big or small reward) which stays constant across trials within a block.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that animals shift their decision boundary even without reward amount manipulations in perceptual decision tasks ( Lak et al, 2020a ). These shifts occur on a trial-by-trial basis, following a win-stay strategy, choosing the same side when that side was associated with reward in the previous trial, particularly when the stimulus was more ambiguous ( Lak et al, 2020a ). In the current task design, however, the optimal bias is primarily determined by the sizes of reward (more specifically, which side delivered a big or small reward) which stays constant across trials within a block.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of the influence of confidence on choice repetition in forced-choice paradigms have often used proxy measures for confidence, such as pupil dilation, response times, and evidence strength. Notably, a recent study by Lak et al (2020) reported increased choice repetition biases following decisions based on weak sensory evidence and used this sensory evidence strength as a proxy for decision confidence. In disagreement with the explanation by Lak et al (2020) , that low decision confidence boosts choice repetition, we found that low decision confidence, as measured with subjective reports and reaction times, was clearly associated with a decreased probability to repeat the previous choice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that animals shift their decision boundary even without reward amount manipulations in perceptual decision tasks (Lak et al, 2020a). These shifts occur on a trial-by-trial basis, following a win-stay strategy, choosing the same side when that side was associated with reward in the previous trial, particularly when the stimulus was more ambiguous (Lak et al, 2020a). In the current task design, however, the optimal bias is primarily determined by the sizes of reward (more specifically, which side delivered a big or small reward) which stays constant across trials within a session.…”
Section: A Perceptual Decision-making Task With Reward Amount Manipulmentioning
confidence: 99%